The effect of leadership style on professional ethical behavior: An empirical study in cement factory - Khademian, Naghmeh (Journal of Entrepreneurship, Business and Economics, 2016)
This study indicates the theoretical perspective and examines the relevant literature that supports the significance of leadership style and professional ethics among employees. The methodology for con-ducting the study was the use of two quantitative questionnaires aimed at determining the relative contribution that task-oriented and relations-oriented styles of leadership have on different dimen-sions of professional ethical behavior. This study is conducted in a manufacturing company and data were collected from 200 employees working in the cement factory. Firstly, the study revealed the type of leadership in this factory and then examined the relation between the leadership style and ethical behavior. To test the hypothesis structural equations modeling was used. The results showed that simultaneous high relations-oriented and high task-oriented leadership styles (i.e. supportive behav-ior) have significant effect positively on professional ethics among employees. Research paper Reference to this paper should be made as follows: Khademian, N. (2016). “The effect of leadership style on professional ethical behavior: An empirical study in cement factory”, Journal of Entrepre-neurship, Business and Economics, Vol. 4, No. 1, pp. 128–147